Chapter 9 SUICIDE BEREAVEMENT AND POSTVENTION APPROACHES FOR YOUNG PEOPLE IN SCOTLAND - del Carpio, Laura (Taylor & Francis, 2024)
Suicide is a leading cause of death globally, and each suicide can have a profound impact on those grieving the loss, including young people. Suicide loss is a risk factor for adverse health and social outcomes including complicated grief and subsequent suicides. Young people coping with such a death may face additional complexities in their bereavement experience including feelings of guilt, shame, perceived stigma, and rejection given the cause of death, alongside wider challenges relating to unmet health and social needs. Suicide bereavement support, or postvention, has increasingly become recognised as a priority within several countries' suicide prevention approaches. Yet, our understanding of what works in terms of support, and particularly for adolescent age groups, remains unclear and predominantly focuses on professional interventions which neglect the role of the wider political, social, and cultural environment.